Explosive energy release by disruption of current sheets - Lakhina, G.S.; Tsurutani, B.T. (My University, 1998)
Current sheets can occur in almost all cosmic plasmas like planetary magnetospheres, stars, and galaxies. The disruption of current sheets releases the excess magnetic energy stored in the plasma system via magnetic reconnection. Ion tearing mode instability can cause spontaneous disruption of the forced current sheets. It is found that trapped electrons have a strong stabilizing effect on the excitation of this instability. The presence of background turbulence can effectively lead to the untrapping of the electron orbits and thus, facilitate excitation of ion tearing instability. The role of current sheet disruptions in magnetospheric substorms, solar flares and coronal transients are discussed.
Keywords: Current sheets; Cosmic plasmas; Planetary magnetospheres; Solar flares; Explosive energy release